Asymmetric vanadium flow batteries: long lifespan via an anolyte overhang strategy. Issue 43 (25th October 2017) - Mu, Di; Zhao, Yang; Yu, Liwei; Liu, Le; Xi, Jingyu
Abstract : An asymmetric electrolyte design concept is introduced to prolong the cycle life of VFBs, and an aVFB operating with a multiple adding strategy demonstrates a much longer lifespan. Abstract : Fast capacity decay is a serious problem in vanadium flow batteries (VFBs). How to eliminate or slow down capacity fading has become a critical issue for the practical application of VFBs. Herein, the concept of an asymmetric vanadium flow battery (aVFB) is introduced, in which the asymmetric design of a catholyte and an anolyte is used to suppress the capacity decay of the VFB. Based on the comprehensive analysis of the capacity decay and electrolyte imbalance process of the traditional symmetric VFB, it was found that the capacity fading is mainly owing to the loss of the anolyte in the long-term cycling test. Therefore, this work attempts to use excess anolyte ( i.e. 10%, 20% and 30%) to mitigate the capacity decay during the long-term operation of the VFB. To gain deeper insights into the capacity retention mechanism of these novel anolyte overhang aVFBs, long-term cycle performance of the corresponding symmetric overhang VFBs and catholyte overhang aVFBs is investigated for comparison. The optimal excess ratio of anolyte and how to add the excess anolyte are also suggested for future study.